2013
DOI: 10.1161/atvbaha.113.301799
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-Like Receptor 2/6 Agonist Macrophage-Activating Lipopeptide-2 Promotes Reendothelialization and Inhibits Neointima Formation After Vascular Injury

Abstract: Objective-Reendothelialization after vascular injury (ie, balloon angioplasty or stent implantation) is clinically extremely relevant to promote vascular healing. We here investigated the therapeutic potential of the toll-like receptor 2/6 agonist macrophageactivating lipopeptide (MALP)-2 on reendothelialization and neointima formation in a murine model of vascular injury. Approach and Results-The left common carotid artery was electrically injured, and reendothelialization was quantified by Evans blue stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
(42 reference statements)
1
22
0
1
Order By: Relevance
“…In this regard we showed that TLR2/6 stimulation by MALP-2 directly promote angiogenesis, a mechanism that is driven by GM-CSF induction in endothelial cells and monocytes (Grote et al, 2010). Moreover, recent data from our group even demonstrated a therapeutic potential of MALP-2 to accelerate endothelial wound healing after interventional vascular injury (Grote et al, 2013). Interestingly, there are in vitro studies showing that MALP-2 can even stimulate bone resorption by an IL-6-dependent mechanism (Piec et al, 1999).…”
Section: Stimulation Of Mscs Promotes Angiogenesismentioning
confidence: 58%
See 1 more Smart Citation
“…In this regard we showed that TLR2/6 stimulation by MALP-2 directly promote angiogenesis, a mechanism that is driven by GM-CSF induction in endothelial cells and monocytes (Grote et al, 2010). Moreover, recent data from our group even demonstrated a therapeutic potential of MALP-2 to accelerate endothelial wound healing after interventional vascular injury (Grote et al, 2013). Interestingly, there are in vitro studies showing that MALP-2 can even stimulate bone resorption by an IL-6-dependent mechanism (Piec et al, 1999).…”
Section: Stimulation Of Mscs Promotes Angiogenesismentioning
confidence: 58%
“…Recently, we demonstrated that MALP-2 could be even used in a therapeutic manner to restore an endothelial damage after experimental vascular injury (Grote et al, 2013). Thus, the beneficial effect of MALP-2 on vascular regeneration is already well documented in mice.…”
Section: K Grote Et Al Tlr2/6 Stimulation Of Mscs Promotes Angiogenesismentioning
confidence: 96%
“…Notably, in vitro IHR treatment also resulted in TLR6 downregulation on monocyte. TLR2/6 agonist MALP-2 has been demonstrated to promote re-endothelialization and inhibits neointima formation after vascular injury via enhanced proliferation and migration of endothelial cells [33]. Accumulating data suggest that ligation of intracellular TLRs by endogenous ligands released from necrotic cells may result in developing Th2-like responses, as well as in the alternative activation of macrophages (M2), that favor local tissue protection and compensatory cell growth [34].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 protein subsequently contributes to the regulation of monocyte responses to MALP-2, so that monocytes are less likely to generate an excessive inflammatory response. Recently, MALP-2 has been found to improve lung host defenses against infections with mycobacteria (48) and improve reendothelialization in a murine model of experimental vascular injury (49). In addition, MALP-2 can reduce bacteremia and improve bacterial clearance in lung parenchyma (50) and can accelerate wound healing in diabetic mice (51).…”
Section: Discussionmentioning
confidence: 99%